Nilai-Nilai Budaya Upacara Mappacci Dalam Proses Pernikahan Adat Suku Bugis di Desa Labuahan Aji Kecamatan Trano Kabupaten Sumbawa - Nuruddin, Nuruddin; Nahar, Nur (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This study examines the sustainable culture of the Labuhan Aji village community, namely Mappacci at Bugis traditional weddings. Which is where this culture is considered by the community to have an effect on the household that will be fostered by the two prospective brides. The purpose of this research is to know the implementation of Mappacci culture, what values exist in Mappacci culture, and the purpose of Mappacci. Mappacci culture is carried out at night before the wedding which is carried out by the bride and groom, where this mappacci is to purify themselves and release their maiden period, the process of implementing this mappacci culture is this mappacci culture, namely bridal showers, wearing bodo clothes, khatam Al -The Qur'an and the last one with zanji, the utensils provided are candles, pillows, sarongs, banana leaves, jackfruit leaves, and dun pacci. The values that exist in this mappacci culture are the value of chastity, the value of kinship, and the value of honesty